Model of Leadership Style, Self-Efficacy, on Performance and Work Engagement as an Intervening Variable: A Literature Review - Rita Mulyanti; Tubagus Hedi Saepudin; Cut Aviyanti (Dinasti Publisher, 2023)
Purpose fill knowledge gaps in the literature on the relationship between leadership style, self-efficacy, work engagement, and performance, as well as to make theoretical contributions in the fields of management, and human resources by broadening understanding of the factors that influence individual performance in the work environment. The method used qualitatively using existing literature from related research results from reference sources found online. The number of articles as literature there are 25 articles related to the topic of this study, after which it is analyzed comparatively. It is illustrated that the three variables have the influence of one variable with another variable, namely leadership style with performance, self-efficiency with performance and through intervening work engagement variables even though there are only one research result. For the future, these and other variables derived from the literature can be continued and developed in follow-up research to fill existing gaps.